(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2012)
An attempt to comment on the low level of attention to the transpersonal in the journal Existential Analysis. In view of the eminent existentialists who have expressed a personal interest in the spiritual realms, this seems odd. Some possible lines of enquiry are pursued.